Estimating T1 from multichannel variable flip angle SPGR sequences. Issue 6 (17th July 2012) - Trzasko, Joshua D.; Mostardi, Petrice M.; Riederer, Stephen J.; Manduca, Armando
Abstract: Quantitative estimation of T 1 is a challenging but important task inherent to many clinical applications. The most commonly used paradigm for estimating T 1 in vivo involves performing a sequence of spoiled gradient‐recalled echo acquisitions at different flip angles, followed by fitting of an exponential model to the data. Although there has been substantial work comparing different fitting methods, there has been little discussion on how these methods should be applied for data acquired using multichannel receivers. In this note, we demonstrate that the manner in which multichannel data is handled can have a substantial impact on T 1 estimation performance and should be considered equally as important as choice of flip angles or fitting strategy. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.